Validity and inter-rater reliability of ankle motion observed during a single leg squat - Paloma Guillén-Rogel; Cristina San Emeterio; Pedro J. Marín (PeerJ, 2022)
Background The single leg squat (SLS) test is a clinical functional test commonly used to evaluate clinically aberrant movement patterns of the knee. The SLS could be an interesting option to analyze ankle control in the frontal plane during dynamic load analysis. However, to date, there are no studies that have analyzed the associations between the increased subtalar joint pronation by navicular drop (ND) test and ankle control with single leg squat (SLSankle) using a three-point scale. The purpose of this study was to evaluate the reliability of a clinical observation method to assess and determine the relationship between navicular drop (ND) and ankle control on the SLSankle score. Methods A total of fifty-five healthy, physically active (31 females and 24 males) volunteers participated in this study. The degree of subtalar pronation was assessed through the ND test, and the ankle control was defined as the ankle displacement in the frontal plane during the SLS. Results We found good intra-rater and inter-rater agreement during SLSankle, with Kappa values from 0.731 to 0.750. The relationship between the SLSankle and ND was significant ; the Spearman’s rank correlation coefficient was 0.504 (p < 0.05). Conclusions The SLSankle score supplied the clinical practice with a reliable and valid alternative for quantifying foot mobility in comparison to the ND test.